KEBUTUHAN HUTAN KOTA BERDASARKAN EMISI KARBONDIOKSIDA DI KOTA PRABUMULIH PROVINSI SUMATERA SELATAN - Yuniar Pratiwi; Endes Nurfilmarasa Dachlan; Lilik Budi Prasetyo (Graduate School Bogor Agricultural University (SPs IPB), 2016)
Urban forest is one of the green open space shape which requires as O2, CO2 absorb, and it is able to create healty physical environment. Prabumulih is one of the part city in South Sumatera which have acreage 4,344.6 ha with existing urban forest areal ±10 ha.The aims of this research is identifying, predicting the urban forest area necessity based on the total of CO2 emissions, and determining the appropriate location to be prioritized as urban forest. The source of CO2 emission derives from the use of fuel (gasoline, diesel, LPG), agricultural area (rice field), cattle (cows, buffaloes, horses, goats, sheep, and poultry) and citizens. Identification of urban forest priority area is based on characteristic of urban forest. The result of this research indicate CO2 emission in 2014 was 190.64 Gg CO2 with the urban forest area necessity to 3,262.44 ha and CO2 emission was predicted to increase until 2034. The result from of model simulation in this research showed that CO2 emission in 2034 will be predicted to 279.40 Gg CO2 with urban forest area needs to 4,785.98 ha. Urban forest locations with higher priority are in Cambai district, West Prabumulih, East Prabumulih, and North Prabumulih.